Cinema, Space, and Polylocality in a Globalizing China - Zhang, Yingjin (Book collections on Project MUSE., 2010)
"Combining inspired critical insights, original observations, and new information, Cinema, Space, and Polylocality in a Globalizing China is a significant work on current Chinese film and a must-read for film scholars and anyone seriously interested in cinema more generally or contemporary Chinese culture."--Jacket